Answer:
(E) I, II and III
Explanation:
Given,
a@b = a + b - ab ∀ a, b ∈ Z ( set of all integers ),
For solving this question we need to remember the following properties of integers:
- Commutative property of addition
- Additive identity property of addition
- Commutative property of multiplication
- Distributive property of multiplication over addition
I. a@b = a + b - ab,
b@a = b + a - ba = a + b - ab
Thus, a@b = b@a
II. a@0 = a + 0 - a × 0
= a + 0 - 0
= a
III. (a@b)@c = (a@b)+c - (a@b)c
= (a + b - ab) + c - (a + b - ab)c
= a + b - ab + c - ac - bc + abc
= a + b + c - ab - bc - ac + abc,
Now, a@(b@c) = a@( b + c - bc )
= a + (b + c - bc) - a(b+c - bc)
= a + b + c - bc - ab - ac + abc
= a + b + c - ab - bc - ac + abc.
Thus, (a@b)@c = a@(b@c)